Factors Associated with Early Smoking Initiation among Korean Adolescents - Eun Sun So, PhD; Ji Young Yeo, MA (Elsevier, 2015)
Purpose: The aim of this study was to identify factors associated with early initiation of cigarette smoking among Korean adolescents. Methods: A secondary analysis was conducted on the 2012 Korea Youth Risk Behavior Web-based Survey data using Cox proportional hazards regression. Results: Early smoking initiation was associated with being male, having a positive subjective health status, perceiving oneself as thin or average weight (body image), having an average happiness level, being stressed, consuming alcohol, having suicidal ideation, experiencing sexual intercourse, having low or average academic grades, having a parental education level of high school or below, not taking a family trip in the previous 12 months, and having a family that approves of smoking in the home. Conclusions: Interventions targeting the prevention of smoking initiation among adolescents should include individual factors such as health status, body weight, perceived mental health status, health-risk behaviors, and academic characteristics as well as family factors that reinforce family cohesion and home smoking bans. Moreover, male adolescents aged 12-13 years and their parents should be the main target of these interventions.